THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT IN THE EFFECT OF PERCEIVED TRAINING BENEFITS AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE (A STUDY AT PT. MODERN INDUSTRIAL ESTATE) - Ecih Suhersih; Fauji Sanusi; Roni Kambara (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the effect of perceived benefits of training and job satisfaction on employee performance, as well as the mediating role of organizational Commitment at PT. Modern Industrial Estate. Data were collected from 72 respondents through questionnaires and performance assessments conducted between 2021 and 2023. The analysis used Structural Equation Modeling (SEM). The results show that the perceived benefits of training do not have a direct effect on performance, but have a positive effect on organizational Commitment. Job satisfaction has a positive effect on performance and organizational Commitment. Organizational Commitment also affects performance and mediates the effects of training benefits and job satisfaction. It is recommended that companies optimize training, create a conducive work environment, and strengthen Commitment through open communication and employee participation.